Management and outcome of patients with gastrointestinal cutaneous fistula in Al-Karama teaching hospital - Surriah, Mohammed Hillu; Bakkour, Amine Mohammed; Hassan, Ahmed Nafi (International Surgery Journal, 2018)
Background: Gastrointestinal cutaneous fistulae are abnormal communication between stomach, small or large bowel, and the skin allowing the gastrointestinal contents to flow onto the skin. It is one of the most dreaded postoperative complications. It is a major cause of morbidity and possible mortality especially in high output fistulae. The aim of this study was to assess the pattern of postoperative gut fistulae particularly on the clinical presentation, diagnostic, work up, managements, and outcomes. Methods: It was a prospective non-randomized study of 52 consecutive patients collected in three and half years (from 1st January 2015 to 1st June 2018) in Al-Karama Teaching Hospital. The study involved patients who had postoperative fistula in the anterior abdominal wall. Originating from the digestive tract. All the patients were subjected to history and physical examination according to a data collection sheet. Results: There were 32 males and 20 females mean age 40.96 and the mean hospital stay (14-45) days. Author found that 42.3% of cases were due to malignancy, around 30.7% were presented following laparotomy for trauma, three cases (5.8%) is due to surgery for inflammatory bowel disease (total colectomy), and 21.2% were due to miscellaneous. Regarding site of fistula, fourteen cases had single fistulae draining from midline laparotomy incision (26.9%). ten cases (19.3%) were miscellaneous conditions. Wound dehiscence and wound infection occurred in four cases (7.7%). Multiple Organ Failure (MOF) occurred in three cases and led to death. Conclusions: Trauma and malignancy made the major two causes of postoperative fistulae in this study. The higher output fistula, the more incidence of complications, such as sepsis, electrolyte disturbances, skin excoriation and weight loss.